Human–AI Collaboration Readiness Across Generations: The Roles of Digital Skills, Growth Mindset, and Organizational Support - Wahdaniah Wahdaniah; Ayyub Yunus; Mujirin M. Yamin (Vifada Management and Social Sciences, 2026)
Purpose: This study examines the simultaneous effects of digital skills, growth mindset, and organizational support on human–AI collaboration readiness among multigenerational academic workers, with generational cohort as a moderating variable. Research Method: A sequential explanatory mixed-method design was employed. Quantitative data were collected from 280 academic workers at a public university in Indonesia using stratified random sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The quantitative findings were further explored through semi-structured interviews with 12 key informants representing Generation X, Millennials, and Generation Z. Results and Discussion: Organizational support emerged as the strongest and most consistent predictor of human–AI collaboration readiness across generations (β = 0.384; p < 0.001). Generational cohort significantly moderated the effects of digital skills (β = 0.110; p = 0.041) and growth mindset (β = 0.154; p = 0.004), with stronger effects among Generation Z workers. This pattern is identified as the “Generation Z Acceleration Effect.” The model explained 62.4% of the variance in collaboration readiness. Implications: The findings support generationally differentiated HR interventions for strengthening human–AI collaboration in higher education and contribute to SDGs 4, 8, and 9. Originality: This study integrates individual capabilities, psychological orientation, organizational support, and generational differences into a unified model of human–AI collaboration readiness and introduces the Generation Z Acceleration Effect.